A mitochondria-related signature for predicting immune microenvironment and therapeutic response in osteosarcoma - Zhang, Lina; Wu, Song; Huang, Junjie; Shi, Yanbin; Yin, Yuesong; Cao, Xu (Frontiers in Oncology, 2022)
Background Osteosarcoma remains to be the most devastating malignant tumor in children and teenagers. Mitochondria have also been proven to play critical roles in osteosarcoma. However, a mitochondria-related signature has been established in osteosarcoma to comprehensively evaluate the pathogenic roles and regulatory roles of mitochondria in osteosarcoma. Methods In this study, osteosarcoma samples' transcriptome data and clinical information were collected from Therapeutically Applicable Research to Generate Effective Treatments (TARGET) and Gene Expression Omnibus (GEO) databases. A comprehensive bioinformatics analysis was performed on the samples at the bulk RNA sequencing level and single-cell RNA sequencing (scRNA-seq) level. EdU, Transwell, and immunohistochemistry (IHC) were performed on PCCB. Results A mitochondria-related signature was constructed in osteosarcoma patients. The prognostic value of the mitochondria-related signature was explored. The predictive value of the mitochondria-related signature in the immune microenvironment and chemotherapy agents was explored. The association between mitochondria and immunity in the tumor microenvironment of osteosarcoma at the scRNA-seq level was investigated. The tumorigenic role of the critical mitochondria-related gene, PCCB, was verified by in vitro validation. Conclusion In conclusion, a mitochondria-related signature was developed in osteosarcoma with solid predictive values in the immune microenvironment, chemotherapy agents, and prognosis.